Examining the effect of logistics service quality on customer satisfaction and re-use intention - Xiaofang Lin; Abdullah Al Mamun; Qing Yang; Mohammad Masukujjaman (PLoS ONE, 2023)
For logistics service providers (LSPs), improving customer satisfaction and obtaining customer re-use intention are key to gaining sustainable competitive advantages and success. Logistics service quality (LSQ) is a concern for logistics service providers, retailers, and customers. The proposed model, which is based on the stimuli-organism-response theory and the logistics service quality framework, integrates operational quality, resource quality, information quality, personal contact quality, customization quality, and customer satisfaction to study logistics service re-use intentions. The data were obtained from an online survey using a structured questionnaire given to those with experience in logistics service. Using partial least squares structural equation modeling on 810 respondents who were adult Chinese customers, this study discovered that operational, resource, information, personal contact, and customization qualities positively affect the satisfaction of logistics service customers, while customer satisfaction positively affects re-use intention. Moreover, the results of the mediation analysis revealed that customer satisfaction mediated the connection between the five components of LSQ and the re-use intention of logistics services. The originality of the study lies in its comprehensive examination of the direct and indirect effects of service quality dimensions on customer satisfaction and logistics service re-use intention in the context of logistics services. This study provides valuable insights into the importance of customer satisfaction in the logistics industry and highlights the need for logistics companies to prioritize customer satisfaction and improve their overall performance and competitiveness.